Effect of a Cooperation Strategy between Primary Care Physicians and Hospital Liver Units on HBV Care in Campania, Italy. (26th July 2018) - Zampino, Rosa; Capoluongo, Nicolina; Boemio, Adriana; Macera, Margherita; Vitrone, Martina; Adinolfi, Luigi Elio; Filippini, Pietro; Sagnelli, Evangelista; Sagnelli, Caterina; Durante-Mangoni, Emanuele; Coppola, Nicola
Abstract : Aims . This study is aimed at assessing the efficacy of an active search and treat strategy for HBV-infected subjects in an endemic area (Campania, Italy). To do this, we created a cooperation bundle between 24 General Practitioners (GPs) and 3 Hospital Liver Units (HLU). We assessed whether this strategy improved the detection of HBV infection in patients at risk and the overall quality of care, with the aim of reducing liver disease progression. Methods . We estimated that, among about 20, 000 patients cared for by the 24 GPs, approximately 280 patients unaware of or underestimating HBV infection would be found. Identified patients were to be referred to the HLU for clinical evaluation and treatment from February 2016 for 12 months. Results . Unexpectedly, screening and enrolment were poor (48 patients only). GP workloads, patient financial difficulties, and patients' refusal were the major causes of enrolment failure according to GPs. All patients referred to HLU completed the program; most of them were HBV inactive carriers. Conclusions . This program failed to scavenge chronic HBV-infected patients in an endemic area and establish a successful clinical collaboration between GPs and HLU. Underlying reasons are diverse and call for new strategies to implement cooperation between primary care providers and hospital specialists.